(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The primary use of this tool is to assist in calibrating the degree of clinical suspicion for a diagnosis, aiding in either confirming or excluding it. Additionally, it is employed for the purpose of illness monitoring. The amount of clinical suspicion and the probability of a specific test result might be positively associated in practical terms. Materials and Methods: The proposed method used to build the website is Visual Studio 2015 with SQL server Database to provide the possibility of electronic interaction and communication between the patient and the laboratory official, through prior online reservation and it is possible to create an account for the patient as well, allowing him to access information about blood analysis within the laboratory as well as the ability to print the report in the form of a paper report. Results: The proposed system website provides the ability to test blood for eight of the common blood test methods, represented by the following tests: Knowing the blood type (ABO), white blood cell count (WBC) / red blood cell number, platelet count, erythrocyte sedimentation time (ESR), estimation of hemoclopane (HB) to sixth experiment, hematocrit determination (PVC), The seventh experiment measured bleeding time (BTE). Conclusion: The current study is able to provide fast, accurate, and detailed analysis of blood samples without the need for manual processing and it leads to cost savings for healthcare facilities in the long run.